PENERAPAN MODEL DISCOVERY LEARNING BERBASIS PENDEKATAN SAINTIFIK UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS XI IPA1 PADA MATERI HIDROKARBON - Nurhalija, Wa Ode Siti; Ratna, Ratna; Marhadi, Muh. Alim (Jurnal Pendidikan Kimia FKIP Universitas Halu Oleo, 2021)
Research has been carried out to improve student learning outcomes XI IPA1 SMA Negeri 1 Bone through a discovery learning model based on a scientific approach to hydrocarbon material. This study aims to, 1) determine the description of the learning outcomes of class XI IPA1 SMA Negeri 1 Bone on hydrocarbon material throgh the application of discovery learning based on a scientific approach, 2) to determine  the  effectiveneness  of  discovery  learning  model  based  on  scientific approach to improving learning outcomes in class XI IPA1 SMA Negeri 1 Bone on hydrocarbon  material,  3)  knowing  the  implementation  of  learning  hydrocarbon material with the application of discovery learning model based on the scientific approach  in  SMA  Negeri  1  Bone,  4)  knowing  the  students’  response  to  the application  of  discovery  learning  model  based  on  the  scientific  approach  to hydrocarbon materia. The data collection technique was done by giving pre-test and post-test with research instruments in the form of multiple choice questions totaling 20 items, student activity observation sheets, teacher activity observation sheets,  and  questionnaire  sheets  or  student  responses  to  the  learning  process. Student  learning  outcomes  with  discovery learning  models obtained  an average value of 79,13. There is an increase in student learning outcomes using discovery learning models based on a scientific approach. This can be seen through the N- Gain analysis, it can be stated that the discovery learning  model with a scientific approach can improve student learning outcomes by obtaining an average value of 0,68.